DESCRIPTIVE ANALYSIS OF SOCIAL MEDIA INFLUENCERS ON CONSUMER PURCHASING DECISIONS: A QUALITATIVE STUDY - Nanoti, Neeraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Influencers on social media have grown in importance since they have the ability to affect consumers' impressions of brands and their purchase habits via their participation, authenticity, and trustworthiness. Using theme analysis and in-depth interviews, this qualitative research investigates how social media influencers affect consumers' decision-making processes. Important aspects that motivate consumers to connect with influencers are examined in the study, including trust, relatability, knowledge, and social proof. According to the results, people are more inclined to buy things recommended by influencers they see as genuine and well-informed. The report also notes that various types of influencers have varying effects on consumers' choices to buy, with micro and nano influencers often generating more engagement since their followers see them as more approachable and having more intimate relationships with them. Parasocial interactions and peer pressure are two of the emotional and psychological processes that the research finds to have a role in consumers' dependence on influencer recommendations. The study also finds out how companies use influencers in a smart way to boost conversion rates, brand loyalty, and recognition. While influencer marketing has many potential benefits, the results show that it may lose some of its lustre when used in an overly commercialised or opaque manner. For marketers, companies, and lawmakers looking to adjust influencer marketing tactics to meet changing customer expectations, the report is a great resource. Companies may create more honest and efficient marketing efforts that win the trust and loyalty of customers for the long haul if they take the time to learn how influencers affect consumers' buying habits.